2017
DOI: 10.1002/ijc.30908
|View full text |Cite
|
Sign up to set email alerts
|

Digitalis use and lung cancer risk by histological type in men

Abstract: Lung cancer risk and tumor characteristics differ between sexes. Estrogen has been suggested to counteract lung cancer development. We aimed to test the hypothesis that digitalis use decreases lung cancer risk due to its estrogenic and other anticancer properties in men. This was a nationwide Swedish population-based cohort study between July 1, 2005 and December 31, 2013. Data on the use of digitalis and organic nitrates in all male individuals were derived from the Swedish Prescribed Drug Registry. New lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Moreover, digoxin decreases the expression of VEGF and NDRG1 through inhibition of HIF-1alpha synthesis 5 and induces autophagy through the regulation of mTOR and ERK1/2 signaling pathways in non-small cell lung cancer cells 6 . A Swedish study observed that digoxin users had a diminished risk of lung neoplasms (HR 0.55, 95% CI 0.39–0.79) compared to users of organic nitrates 30 . Nonetheless, these chemopreventive features of digoxin did not translate into diminished lung cancer mortality in our large population-based study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, digoxin decreases the expression of VEGF and NDRG1 through inhibition of HIF-1alpha synthesis 5 and induces autophagy through the regulation of mTOR and ERK1/2 signaling pathways in non-small cell lung cancer cells 6 . A Swedish study observed that digoxin users had a diminished risk of lung neoplasms (HR 0.55, 95% CI 0.39–0.79) compared to users of organic nitrates 30 . Nonetheless, these chemopreventive features of digoxin did not translate into diminished lung cancer mortality in our large population-based study.…”
Section: Discussionmentioning
confidence: 99%
“…However, because such exposure misclassification would have affected all cohort members similarly, regardless of the outcome of interest, this bias is probably non-differential (independent of the outcome) and would thus result in underestimated associations between exposures and outcomes rather than explaining them. In addition, because a prescription is valid for a maximum of 12 months in Sweden, it is possible to define an ‘incident’ exposed group of participants by excluding those with a first known prescription in the first year of the cohort establishment and explore the exposure-response association in these ‘incident’ exposed participants 21 22. Although the lack of data on medication use before 2005 challenges whether these ‘incident’ users are first-time users or re-starters, linkage to other registers may provide useful information, for example, date of first diagnosis as recorded in the Patient Register (initiated in 1965 and nationwide complete from 1987), for selecting study participants or conducing sensitivity analyses.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%